The Fast and Simple LC-MS/MS Method for Determination of Rifampicin in the Human Blood Plasma - Baskaran, V; Chaithanya Sudha, P. D.; Abishek, T; Hariesh Kumar, R; Ramesh, G; Dang, Raman (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Rifampicin is an important anti tuberculosis drug for the early infection and, more importantly, bactericidal activity against mycobacterium tuberculosis. LC-MS/MS, with the required molecular specificity, provides quantitative method to rapidly differentiate between the drugs and their metabolites. Aim The current study represents the fast and simple LC-MS/MS method for determination of rifampicin in the human blood plasma. Materials and Methods The plasma samples containing the rifampicin drug were cleaned up by using the protein precipitation method. The chromatographic division was performed by utilizing the ZORBAX Eclipse plus C18 Column (4.6 mm X 150 mm, 5μm). The versatile stage comprised of acetonitrile and 10 Mm ammonium acetic acid derivation in a proportion of 80:20% V/V, wash the column with the blend of solvents comprising of acetonitrile and water 80:20% V/V, maintaining column oven temperature at 30°C±1°C and the auto sampler temperature is kept up with at 10°C±1°C. The injection volume of the sample is 10.0 μL and the total run time of the experiment is 4 min with a flow rate of 1000 mL/min and with a split ratio of 50:50 for the entire experiment. Results and Discussion An LC-MS/MS method for the rifampicin from the sample was performed. Sample volume of 0.300 ml, the injection volume is taken as 10.0 μL and total run time is 4 min, RT for rifampicin is 1.30±0.5 min and the reference drug roxithromycin RT is 3.00±0.5 min. Conclusion The transient LC-MS/MS study permits the assessment of enormous quantities of blood tests in a brief timeframe with fast, simple and successful readiness, giving a quick, dependable and best device for RIF clinical observing and review.
Keywords: Rifampicin; LC-MS/MS; Protein precipitation; Acetonitrile